Identifikasi Karakteristik Konselor Efektif Berdasarkan Tokoh Punakawan Bagong - Wahyu Nanda ES (Jurnal Konseling dan Pendidikan, 2016)
Bagong is Punakawan figure. Bagong is one of the local wisdom that comes from Indonesia. Bagong have various characteristics sublime. The purpose of this study was to describe the characteristics of Bagong. Characteristics of Bagong can be referred to a counselor to develop the characteristics of an effective counselor. The identification results show the characteristics of an effective counselor based Bagong figure are (1) genuine; (2) has a sense of humor; (3) the wise in responding to the phenomenon; (4) simple and patient in serving the counselee; (5) honesty; (6) have the view that every individual has a deficiency; (7) has the ability to see a difference value; and (8) gives the freedom to counselee for decision making.